Pelaksanaan Promosi Digital Menggunakan Media Blog Pada UMKM di Kelurahan Sumurwelut Kecamatan Lakarsantri Kota Surabaya - Madona Diadora; Jojok Dwirido Tjahjono (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The implementation aims to investigate and analyze the application of digital promotion using blog media for UMKM in Sumurwelut Village, Lakarsantri District, Surabaya City. Through a qualitative approach and case study design, this study explores the extent to which UMKM in the village use blogs as a digital promotion tool. The results indicate that UMKM have generally adopted digital promotion strategies through blogs with content involving product descriptions, customer reviews, special offers, and industry-related articles. UMKM that are active in creating high-quality content through blogs experience a significant increase in visibility and sales. Supporting factors include a good understanding of the blog platform, the involvement of UMKM owners, and creativity in presenting content. Technical obstacles, and lack of understanding of the benefits of digital promotion are the main obstacles. The positive response from consumers to digital promotion through blogs shows increased trust, and a tendency to interact further. These findings provide deep insights into the effectiveness of digital promotion in UMKM and refer to recommendations for the development of better digital promotion strategies, including increasing UMKM' understanding of the potential of digital promotion and optimizing interaction with consumers through blog platforms. It is expected that this internship will make a significant contribution to stakeholders, including UMKM, local governments, and UMKM supporting institutions, in supporting UMKM business growth in the digital era.